The Role of Parasocial Relationships, Congruence and Source Credibility in Indonesia: A Study on Tiktok Live Streaming Commerce in the Cosmetics Industry - Caroline Lawrence; Bryna Meivitawanli (Australasian Accounting, Business and Finance Journal, 2023)
This study aimed to investigate how parasocial relationships, congruence, and source credibility influence purchase intention in TikTok Live Streaming commerce for cosmetics among Indonesian Generation Z users. Data was collected from 270 respondents through an online questionnaire, and validity and reliability tests were conducted. The data were analyzed using Structural Equation Modeling (SEM-PLS). Results showed that celebrity endorsers' attractiveness, trustworthiness, and expertise positively impact purchase intention. Parasocial relationship mediated the connection between celebrity characteristics and purchase intention. Moreover, celebrity-product congruence positively influenced endorsers' perceived credibility and mediated the relationship with purchase intention. The findings emphasize the importance of celebrity attractiveness, trustworthiness, and expertise in shaping purchase intention. The mediating role of parasocial relationships highlights the significance of strong celebrity-audience connections. Additionally, celebrity-product congruence enhances endorsers' credibility and positively influences purchase intention. These insights assist brands and marketers in optimizing influencer marketing strategies on TikTok, fostering engagement and driving purchase behavior.
Keywords: Congruence; Internet celebrity; Match-up hypothesis; Parasocial relationships; Source credibility; TikTok Live streaming